2013
DOI: 10.21608/zumj.2013.4300
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Liver Type-Fatty Acid Binding Protein and Plasma Cystatin C as Early Predictors of Contrast Induced Acute Kidney Injury

Abstract: Background: Contrast-induced acute kidney injury (CI-AKI) continues to have an increasing incidence, representing the third most common cause of hospital acquired acute kidney injury. It is a syndrome in which an acute renal dysfunction is diagnosed after the intravascular injection of contrast media. Acute renal injury is typically diagnosed by measuring serum creatinine that is an unreliable indicator during acute changes in kidney function; thus, the need for early sensitive biomarkers to detect acute kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Regarding serum creatinine criteria which was utilized in the present study, clinical AKI is identified when serum creatinine is increased at least 0.3 mg/dL higher than the baseline level within 48 hours or 150% of baseline within 7 days. Despite having normal serum creatinine, subclinical AKI could be diagnosed by novel kidney injury biomarkers including uNGAL level more than 150 ng/mL or uL‐FABP level above 10.5 ng/mL . No AKI was established when uNGAL level was lower than 150 ng/mL or uL‐FABP level was below 10.5 ng/mL…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding serum creatinine criteria which was utilized in the present study, clinical AKI is identified when serum creatinine is increased at least 0.3 mg/dL higher than the baseline level within 48 hours or 150% of baseline within 7 days. Despite having normal serum creatinine, subclinical AKI could be diagnosed by novel kidney injury biomarkers including uNGAL level more than 150 ng/mL or uL‐FABP level above 10.5 ng/mL . No AKI was established when uNGAL level was lower than 150 ng/mL or uL‐FABP level was below 10.5 ng/mL…”
Section: Methodsmentioning
confidence: 99%
“…Despite having normal serum creatinine, subclinical AKI could be diagnosed by novel kidney injury biomarkers including uNGAL level more than 150 ng/mL 10,11 or uL-FABP level above 10.5 ng/mL. 12 No AKI was established when uNGAL level was lower than 150 ng/mL or uL-FABP level was below 10.5 ng/mL Serum creatinine and urine samples were collected at baseline before starting CMS (day 0), and at day 5 and 7 after CMS prescription ( Figure 1). The patients received CMS in a loading dose within 24 hours and then the dose adjustment was prescribed on the following days.…”
mentioning
confidence: 99%